VEEG monitoring and electrographic seizures in 232 pediatric patients in ICU at a tertiary hospital in China - Sang, Tian; Wang, Ying; Wu, Ye; Guan, Qiao; Yang, ZhiXian (Frontiers in Neurology, 2022)
Objectives To investigate neonatal electroencephalography (EEG) background activity and electrographic seizures in patients in the pediatric intensive care unit (PICU) who underwent bedside video-electroencephalography (vEEG) monitoring. Methods A total of 232 pediatric patients admitted or transferred to PICU that underwent vEEG monitoring were retrospectively enrolled in this study, and electrographic status epilepticus was observed after vEEG monitoring. Results The median age was 1.56 years [95% confidence interval (CI) = 1.12–2.44]. Electrographic seizures occurred in 88 patients (37.9%), out of which 36 cases (40.9%) had electrographic status epilepticus. Prior epileptic encephalopathy diagnosis [odds ratio (OR) = 6.57, 95% CI = 1.91–22.59, p = 0.003], interictal epileptiform discharges (OR = 46.82, 95%CI = 5.31–412.86, p = 0.0005), slow disorganized EEG background (OR = 11.92, 95%CI = 1.31–108.71, p = 0.028), and burst-suppression EEG background (OR = 23.64, 95%CI = 1.71–327.57, p = 0.018) were the risk factors for electrographic seizures' occurrence. Of the 232 patients, the condition of 179 (77.2%) patients improved and they were discharged, 34 cases (14.7%) were withdrawn, and 18 cases (7.8%) died. The in-hospital death rate was 47.6% (10 in 21 cases) in patients with attenuated/featureless, compared to 0/23 with normal EEG background. Conclusions Electrographic status epilepticus occurs in more than one-third of patients with electrographic seizures. vEEG is an efficient method to determine electrographic seizures in children. Abnormal EEG background activity is associated with both electrographic seizures' occurrence and unfavorable in-hospital outcomes.